2016
DOI: 10.3402/fnr.v60.30472
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae as a safe food source for animals: nutritional characteristics of the acidophilic microalgaCoccomyxa onubensis

Abstract: BackgroundEdible microalgae are marine or fresh water mesophilic species. Although the harvesting of microalgae offers an abundance of opportunities to the food and pharmaceutical industries, the possibility to use extremophilic microalgae as a food source for animals is not well-documented.ObjectiveWe studied the effects of dietary supplementation of a powdered form of the acidophilic microalga Coccomyxa onubensis on growth and health parameters of laboratory rats.MethodFour randomly organized groups of rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 39 publications
0
16
0
2
Order By: Relevance
“…Feed stocks containing higher concentrations of methionine and lysine have been found to increase chicken breast and thigh muscles and improve the quality and quantity of meat. Microalgae also produce bioactive peptides with antioxidative, antihypertensive, anticoagulative, antitumor and immune-simulative properties [ 11 , 36 ]. The most widely used microalgae for protein-rich feed supplements include species of Chlorella , Arthrospira , Dunaliella , Tetraselmis , Phaeodactylum , Skeletonema , and Scenedesmus [ 37 , 38 ].…”
Section: Microalgal Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feed stocks containing higher concentrations of methionine and lysine have been found to increase chicken breast and thigh muscles and improve the quality and quantity of meat. Microalgae also produce bioactive peptides with antioxidative, antihypertensive, anticoagulative, antitumor and immune-simulative properties [ 11 , 36 ]. The most widely used microalgae for protein-rich feed supplements include species of Chlorella , Arthrospira , Dunaliella , Tetraselmis , Phaeodactylum , Skeletonema , and Scenedesmus [ 37 , 38 ].…”
Section: Microalgal Compoundsmentioning
confidence: 99%
“…Moreover, it was stated that microalgae feed-supplement (i) presents cholesterol-lowering effect in animals, (ii) improves immune response [ 4 ], (iii) enhances milk quality and production yield in cows [ 5 ], (iv) promotes animal growth and improves meat and egg quality [ 6 ], (v) offers resistance to disease through antiviral and antibacterial action [ 7 ], (vi) improves gut function [ 8 ], (vii) enriches the colonization of probiotics [ 8 , 9 ] and increases feed conversion [ 10 ]. Furthermore, it was recently proved that algae-based feed increases reproductive performance and helps in weight control [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the potential applications of this microalga, an antibacterial effect against human pathogens has been reported by Navarro et al [13], and microalgal fatty acids were suggested to be involved in the antibacterial activity. Although the mechanisms through which fatty acids may exert bactericidal activity are not fully understood, it has been reported they may promote membrane damage resulting in nutrient uptake alteration and cellular respiration inhibition [14]. In addition, this microalga could be also attractive as a nutritional supplement for food and feed industries [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms through which fatty acids may exert bactericidal activity are not fully understood, it has been reported they may promote membrane damage resulting in nutrient uptake alteration and cellular respiration inhibition [14]. In addition, this microalga could be also attractive as a nutritional supplement for food and feed industries [14]. These data indicate the potential of C. onubensis as source of valuable compounds and highlight the interest of producing its biomass at large-scale.…”
Section: Introductionmentioning
confidence: 99%
“…На территории Российской Федерации хлорелла употребляется в качестве самостоятельной биологически активной добавки, а не ингредиента для приготовления кулинарной продукции и блюд. Одна из причин возникновения данного явления в нашей стране -недостаточный уровень знаний о хлорелле и её свойствах, в отличие от Японии, где хлореллу часто применяют в промышленных масштабах пищевых направлений [11]. Российский потребитель знаком с хлореллой только как с полноценным продуктом, который употребляется непосредственно внутрь без проведения дополнительных операций.…”
Section: Introductionunclassified